A ghost tale for Christmas time (New York City Random House, Inc., 2010)
Jack and Annie travel back to Victorian London when Merlin asks them to use their magic to inspire Charles Dickens to write "A Christmas Carol".
Time travel-Fiction.
Magic-Ficiton.